Analysis of Sustainable Utilization of Water Resources in 11 Coastal Provinces or Municipalities Based on Ecological Footprint of Water Resources - YANG Tingting (Renmin Zhujiang)
The ecological footprint,ecological carrying capacity,and sustainable utilization of water resources in 11 coastal provinces or municipalities in China from 2005 to 2020 are analyzed based on the ecological footprint model of water resources.The results show that:①Firstly,the changing trend of the ecological footprint of water resource is similar to that of water environment,with a W-shaped pattern;the proportion of ecological footprint of water environment is the highest among the three types of ecological footprint accounts of water resources,indicating that ecological footprint of water environment is the main source of that of water resources;②Among the four types of ecological footprint of freshwater,the ecological footprint of agricultural water consumption accounts for the highest proportion of the total ecological footprint of the freshwater and is much higher than the ecological footprint of water consumption for industry,living,and ecology (except Shanghai).This indicates that the ecological footprint of of agricultural water consumption is the main contribution type of the ecological footprint of freshwater;③Affected by natural and social factors,the ecological carrying capacity of water resources fluctuates obviously,showing a distribution pattern of high in the south and low in the north;④The water resources are in the ecological deficit state on the whole.Only Guangxi Province has been in the ecological surplus state of water resources during the study period.The load index of water resources shows an increasing trend and is above grade II,which indicates that the utilization degree of water resources is high,with small potential,but the development and utilization are difficult.The ecological footprint of water resources per 10 000 yuan GDP shows a downward trend,and the utilization efficiency of water resources continues to improve,so the sustainable utilization of water resources is possible.